Ipteks Bagi Masyarakat Kelompok Usaha Makanan di Kota Bukittinggi - Ratni Prima Lita; Laura Syahrul; Yulia Henri Yeni (Warta Pengabdian Andalas, 2017)
“Ummi Aufa Hakim” and “Ra Bread” group in Bukittinggi has various limitations in running a business, particularly the ability of its resources (human resources, marketing, and finance management). The activity have the objective as folows: To develop ability businessman and employee of finance to arrange financial statement with aplicate of software. To provide the business consultation for relating to the marketing of e-commerce activities, particularly products promotion. The method of this activity has done in several ways: training and business consultation. “Ummi Aufa Hakim” and “Ra Bread” group in Bukittinggi as the object of this activity. They are active and interest to arrange financial statement and developing an e-commerce website as marketing media of businessman products. Website has arrange of this activity of “www.ummi-aufa-hakim-bukittinggi.com and www.toko-roti-rabread-bukittinggi.com.